2022
DOI: 10.1108/jfm-02-2022-0019
|View full text |Cite
|
Sign up to set email alerts
|

Indirect effect of extra-industry network and innovativeness on performance through proactiveness

Abstract: Purpose The current study aims to advance the research on the extra-industry network, innovativeness and performance of small and medium enterprises (SMEs) by examining the mediation role of proactiveness. The study also aims to examine the mediating role innovativeness between extra-industry network and performance. Design/methodology/approach This study used the proportionate stratified random sampling method to select the study sample and the questionnaire survey approach to 580 SMEs. A total of 150 compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 100 publications
1
22
0
Order By: Relevance
“…Firms should therefore prioritize knowledge in relation to customers and suppliers' needs and demands to improve their performance and profits by practicing intense interplay, personal visits, frequent communication, and insights into the working of foreign markets (Jalali et al, 2022). Forsgren (2002, p.264) suggested that "a special aspects of learning from other organizations is learning through the existing business relationships.…”
Section: Relational Capital and Performancementioning
confidence: 99%
See 4 more Smart Citations
“…Firms should therefore prioritize knowledge in relation to customers and suppliers' needs and demands to improve their performance and profits by practicing intense interplay, personal visits, frequent communication, and insights into the working of foreign markets (Jalali et al, 2022). Forsgren (2002, p.264) suggested that "a special aspects of learning from other organizations is learning through the existing business relationships.…”
Section: Relational Capital and Performancementioning
confidence: 99%
“…Proactiveness is defined as acting opportunistically to shape the environment by influencing trends, creating demand, and becoming a first mover in a competitive market (Jalali & Jaafar, 2019;Lumpkin & Dess, 1996). Proactiveness is necessary for competitive advantage (Brendle, 2001) where it provides opportunities-based knowledge pertaining competitors and initiatives (Zahra & Covin, 1995) and it return, enables the ability of controlling the market network distribution and establishing brand recognition (Jalali et al, 2022;Wiklund & Shepherd, 2005).…”
Section: Eo and Performancementioning
confidence: 99%
See 3 more Smart Citations